OPTIMIZING SOCIAL MEDIA AS A PUBLIC RELATIONS TOOL IN EDUCATIONAL INSTITUTIONS - Ramadhina, Marini Shadrina (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research analyzes the role of social media as a public relations tool in educational institutions in the context of the digital era. The background to this research is the rapid development of technology which is changing society's communication patterns and the need for educational institutions to build closer relationships with their communities. The aim of the research is to identify social media optimization strategies, opportunities and challenges faced by educational institutions in utilizing this platform. The method used is a literature study with a descriptive-analytical approach, examining various theories and previous research results. The research results show that social media has great potential in supporting public relations functions, such as conveying information quickly and efficiently, building a positive image, and strengthening two-way communication with various stakeholders. However, optimizing social media faces challenges such as limited competent human resources, difficulty maintaining content consistency, and online reputation risks due to the spread of negative information. In conclusion, social media is a strategic tool to increase the visibility, reputation and relationship of educational institutions with the community. Effective implementation requires a strategic approach, professional management, and the use of the latest technology to overcome existing challenges.